2020
DOI: 10.1111/1750-3841.15096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tea polyphenols on the oral and intravenous pharmacokinetics of ticagrelor in rats and its in vitro metabolism

Abstract: Green tea is widely consumed as a beverage and/or dietary supplement worldwide, resulting in the difficulty to avoid the comedication with ticagrelor for acute coronary syndrome (ACS) patients receiving antiplatelet therapy. This study was designed to investigate the effect of the most abundant content in green tea, tea polyphenols on the oral and intravenous pharmacokinetics of ticagrelor in rats and its in vitro metabolism. Rats were orally treated with either saline or tea polyphenol extracts (TPEs) dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Varying concentrations of DGK, GK, IGK, and AMF incubated for 30 min with gefitinib (10 μM), tamoxifen (20 μM), ticagrelor (30 μM), respectively ( Wang et al, 2020 ). The ExionLC AD HPLC system consisted of an autosampler, a quaternary delivery system and a degasser.…”
Section: Methodsmentioning
confidence: 99%
“…Varying concentrations of DGK, GK, IGK, and AMF incubated for 30 min with gefitinib (10 μM), tamoxifen (20 μM), ticagrelor (30 μM), respectively ( Wang et al, 2020 ). The ExionLC AD HPLC system consisted of an autosampler, a quaternary delivery system and a degasser.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, catechins, the plant flavonoid extracted from green tea, could effectively affect the bioavailability of the substrates of CYP3A (Misaka et al, 2013). Research has shown that tea polyphenols could affect the bioavailability of ticagrelor by regulating the activity of metabolic enzymes (Wang et al, 2020). By contrast, catechins could modulate the ability of P-gp to regulate the transport of drugs (Sugihara et al, 2011).…”
Section: Introductionmentioning
confidence: 99%